POLA ASUH PARENTING STYLE METODE PENGASUHAN DAN PENDIDIKAN PADA ANAK - Ria Rachmawati; Tantohadi, Tantohadi; Ubabuddin , Ubabuddin (CV. ADIBA AISHA AMIRA, 2024)
The personality of a child is determined by several factors: genetic and environmental factors. Parents who are the first environment a child encounters provide a great contribution in shaping the personality of a child. Families have models of parenting as well as methods of providing education. There are three kinds of parenting that parents can apply to children, namely: democratic parenting, permissiveness and authority. Democratic parenting gives children freedom responsibly, while authoritarian parenting is a way of educating children by using authoritarian leadership, that is, parents determine all policies, steps and tasks that must be done. Authoritarian parenting reflects the attitude of parents who act hard and tend to discriminate. Permissive parenting patterns have the characteristics of parents to give full freedom to children to do so that sometimes children do actions that are against the rules. In providing parenting to children, some strategies provide education with exemplary methods, familiarization, attention, advice and methods of punishment.